2019
DOI: 10.1186/s12885-019-5394-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tumor analysis and liquid biopsy: a feasibility investigation analyzing circulating tumor DNA in patients with central nervous system lymphomas

Abstract: Background Central nervous system lymphomas (CNSL) is a devastating disease. Currently, a confirmatory biopsy is required prior to treatment. Objective Our investigation aims to prove the feasibility of a minimally-invasive diagnostic approach for the molecular characterization of CNSL. Methods Tissue biopsies from 6 patients with suspected CNSL were analyzed using a 649gene next-generation sequencing (NGS) tumor panel (tumor vs. reference ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
0
30
0
1
Order By: Relevance
“…An emerging field that may ameliorate some tumor sample issues is the testing of circulating tumor-specific markers. These include circulating tumor cells (CTC) or circulating tumor DNA (ctDNA), as well as RNAs, proteins, or metabolites, that are present in body fluids such as the blood, urine, and peritoneal or cerebrospinal fluid [50][51][52][53][54]. Liquid biopsies are easily accessible through minimally invasive procedures that can be repeated to provide a dynamic and longitudinal assessment of tumor-specific diagnostic, prognostic, or predictive biomarkers.…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…An emerging field that may ameliorate some tumor sample issues is the testing of circulating tumor-specific markers. These include circulating tumor cells (CTC) or circulating tumor DNA (ctDNA), as well as RNAs, proteins, or metabolites, that are present in body fluids such as the blood, urine, and peritoneal or cerebrospinal fluid [50][51][52][53][54]. Liquid biopsies are easily accessible through minimally invasive procedures that can be repeated to provide a dynamic and longitudinal assessment of tumor-specific diagnostic, prognostic, or predictive biomarkers.…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Special cell-stabilizing blood collection tubes have been used to minimize genomic DNA contamination, which allows processing to be delayed for multiple days (Norton et al, 2013;Diaz et al, 2016;Merker et al, 2018). Although some labs are using these for CSF (Hickmann et al, 2019), the practice is not standard, and the value of cell-stabilizing tubes has not been systematically investigated. As with plasma, CSF specimens can be stored frozen after processing, but multiple freeze-thaw cycles should be avoided (Merker et al, 2018).…”
Section: Preanalytical Variablesmentioning
confidence: 99%
“…Multiple methods for purifying cell free DNA exist, but none of these have been systematically studied in CSF. For example, Hickmann et al (2019) reported that in their general experience, the QIAamp Circulating Nucleic Acid Kit provided better results with CSF. Likewise, Huang et al (2017) reported that centrifugation for 10 min at 1000 × g is optimal for selection of DNA fragments of ∼150 bp, but others have not confirmed this.…”
Section: Preanalytical Variablesmentioning
confidence: 99%
“…plasma/serum and lymphatic fluid) but also in all examined body fluids [7]. Among them is urine [8][9][10], cerebrospinal fluid (CSF) [11,12], pleural fluid including ascites [13,14], saliva [15,16], bronchial lavage fluid [17] and the cell-free supernatant from fine needle aspiration of thyroid nodules [18]. The ubiquitous occurrence of cell-free nucleic acids leads one to assume that these molecules might have a biological meaning.…”
Section: Biology Of Cfdnamentioning
confidence: 99%